Avaliação ambiental em um processo de dual sourcing aplicado na indústria automotiva - Souza, Silvio Mauricio de (2016)
With the increase in production worldwide advancing, just as is the increased use of natural resources and therefore have a greater environmental degradation. The economic growth is part of the goals of any nation, but civil society is increasingly concerned with the direction this is taking such growth. Not only society, but also the rulers are concerned with environmental issues and climate change that surround the planet. Companies in turn, also following this environmental movement, seek to reduce the use of natural resources and take measures to minimize the impacts caused by its processes on the environment. One way to do this is to establish an environmental assessment on its suppliers, given that bulk of parts of manufacturers are purchased from the supply chain. However, there are many questions of how an environmental assessment can bring positive and effective results for the company, since recent research indicates that many papers, not certain why the supplier was the best choice or even worse make clear, do not make clear how this particular supplier can improve its environmental classification. This study carried out a comparative environmental assessment of two suppliers in a process of dual sourcing using the Material Input per Units of Service - MIPS as environmental tool. For this study the research methodology used was the case study by means semi-structured interviews, comparing the two processes of suppliers with a process called Reference. The results showed how a supplier is more eco-efficient than other and it was possible to generate a rating for both. In addition, the study allowed the least eco-efficient supplier, which clearly visualize the points in your process could be improved.